IMPROVING THE RULES FOR THE ACCOUNTING OF FOREIGN CURRENCY DIFFERENCES IN UZBEKISTAN - Shakhnoza, Umarova (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The article examines the types of exchange rate differences that arise as a result of transactions with various foreign companies during the financial and economic activities of enterprises and their recognition in the accounting system of the enterprise and according to tax legislation. Method: The methodological basis of the article is based on the laws of our republic, works and reports of our President, decisions of the Cabinet of Ministers, national and international accounting standards, regulations, guidelines, scientific works published abroad and in our republic, textbooks and manuals, scientific consists of articles, internet network materials and practical materials of researched enterprises. The article uses analysis and synthesis, induction and deduction, evaluation, documentation, grouping, comparative analysis of literature and other methods. Results: Based on our national legislation, enterprises recalculate all currency transactions into sums at the exchange rate of the Central Bank of the Republic of Uzbekistan for accounting and taxation purposes. Because the exchange rate is constantly changing, there will be differences between the value of the commodity or property and the payment. Differences result in positive and negative exchange rate differences. If the enterprise paid more money in sums than the price of the goods, it suffered a loss - this is a negative exchange rate difference. And if the company paid less, it will receive a profit in the form of a positive exchange rate difference. This situation is the opposite for importers and exporters (Figure 1). Novelty: Conclusions and suggestions are given on the conducted researches.